Host response mechanisms in periodontal diseases - Nora SILVA; Loreto ABUSLEME; Denisse BRAVO; Nicolás DUTZAN; Jocelyn GARCIA-SESNICH; Rolando VERNAL; Marcela HERNÁNDEZ; Jorge GAMONAL (University of São Paulo, 2015)
Periodontal diseases usually refer to common inflammatory disorders known as gingivitis and periodontitis, which are caused by a pathogenic microbiota in the subgingival biofilm, including Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Tannerella forsythia and Treponema denticola that trigger innate, inflammatory, and adaptive immune responses. These processes result in the destruction of the tissues surrounding and supporting the teeth, and eventually in tissue, bone and finally, tooth loss. The innate immune response constitutes a homeostatic system, which is the first line of defense, and is able to recognize invading microorganisms as non-self, triggering immune responses to eliminate them. In addition to the innate immunity, adaptive immunity cells and characteristic cytokines have been described as important players in the periodontal disease pathogenesis scenario, with a special attention to CD4+ T-cells (T-helper cells). Interestingly, the T cell-mediated adaptive immunity development is highly dependent on innate immunity-associated antigen presenting cells, which after antigen capture undergo into a maturation process and migrate towards the lymph nodes, where they produce distinct patterns of cytokines that will contribute to the subsequent polarization and activation of specific T CD4+ lymphocytes. Skeletal homeostasis depends on a dynamic balance between the activities of the bone-forming osteoblasts (OBLs) and bone-resorbing osteoclasts (OCLs). This balance is tightly controlled by various regulatory systems, such as the endocrine system, and is influenced by the immune system, an osteoimmunological regulation depending on lymphocyte- and macrophage-derived cytokines. All these cytokines and inflammatory mediators are capable of acting alone or in concert, to stimulate periodontal breakdown and collagen destruction via tissue-derived matrix metalloproteinases, a characterization of the progression of periodontitis as a stage that presents a significantly host immune and inflammatory response to the microbial challenge that determine of susceptibility to develop the destructive/progressive periodontitis under the influence of multiple behavioral, environmental and genetic factors.